(untitled) (Eurasian Research Bulletin, 2022)
The article examines the essence of several works on the study of the strength and durability of conveyor belts and the methods of calculating the service life of the belts. By studying and analyzing the previous works, the ways of developing the optimal method of calculating the strength of multi-layer conveyor belts are shown